Uma viagem pela poética de Carlos Drummond de Andrade, (re)tratando a marcante presença de Itabira em sua obra - Rodrigues, Roberto Geraldo (2011)
This work paints the significant presence of the birthplace of Carlos Drummond de Andrade in his literary work. It addresses the intertwined relation between the poet and Itabira, the city of Minas Gerais sung by him in verse and prose, and it has been immortalized in his poem "Confidência do itabirano"(“Confidentiality of Itabirano”). Some say about the "perpetuation" of Itabira which is present in several texts of his vast work and it faces a symbiotic process between Drummond / poetry / Itabira. It reveals the extent of the outstanding heritage steeped in the soul and the work of C.D.A. due to his roots from Itabira/ Minas Gerais and the emergence of another legacy: the geography of Drummond's literature in Itabira. The theoretical argument is based on the critical fortune of Drummond, being used critical and historical studies on the gauche poet. From the work of Domingo Gonzales Cruz No meio do caminho tinha Itabira: ensaio poético sobre as raízes itabiranas na obra de Drummond (Midway had Itabira: poetic essay on the roots of Itabira in the work of Drummond ) it builds a web of poetic dialogues with critics of Drummond's poetic like Affonso Romano de Sant’Anna, Emanuel de Moraes, Davi Arigucci Júnior, Alcides Villaça, José Maria Cançado, Alexandre Pilati and others.